Prospects of ruthenate-based electrodes in metal-ion batteries - Majid, Abdul; Khadim, Bazgha; Alkhedher, Mohammad; Bulut, Niyazi (Royal Soc Chemistry, 2024)
Advancements in energy storage technology have led to the exploration of novel functional materials that have been at the heart of materials science, especially in this century. The distinct physical and electrochemical characteristics of ruthenates and related materials have made them potential candidates for diverse uses and device grade applications. The extensive utilization of ruthenates in metal-ion batteries has been witnessed in the recent past due to their unique structural features, electronic structure, stability, and transport properties. The current technology related to batteries suffers from inadequate storage capacity, cyclic stability, and ionic conductivity, leading to a loss in electrochemical performance, battery longevity and efficiency. The challenges related to stability, cost effectiveness, synthesis complications, and technological aspects are the key difficulties that should be considered by the community while developing the batteries for the future. To address these issues, more consistent efforts are required to ensure scalable, reproducible and controlled synthesis of these materials to fully utilize their potential for applications in rechargeable metal-ion batteries. Herein, we provide a comprehensive overview of the current state of knowledge, opportunities, challenges and future prospects on the utilization of ruthenates and related materials as next-generation materials for high-performance metal-ion batteries. Advancements in energy storage technology have led to the exploration of novel functional materials that have been at the heart of materials science, especially in this century.
Keywords: Negative Thermal-Expansion; Prussian Blue Analogs; Redox-Flow Batteries; Binder-Free Cathode; Electrochemical Performance; Rechargeable Batteries; Bifunctional Catalyst; Air Batteries; K-Ion; Oxide